2011
DOI: 10.1007/s00441-010-1127-9
|View full text |Cite
|
Sign up to set email alerts
|

Origin and hierarchy of basal lamina-forming and -non-forming myogenic cells in mouse skeletal muscle in relation to adhesive capacity and Pax7 expression in vitro

Abstract: As a novel approach to distinguish skeletal myogenic cell populations, basal lamina (BL) formation of myogenic cells was examined in the mouse compensatory enlarged plantaris muscles in vivo and in fiber-bundle cultures in vitro. MyoD(+) myogenic cells located inside the regenerative muscle fiber BL were laminin(-) but interstitial MyoD(+) cells were laminin(+). This was also confirmed by electron microscopy as structural BL formation. Similar trends were observed in the fiber-bundle cultures including satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…This mixture was actually the same as for mouse Sk-MSCs [8], because it is difficult to divide myogenic and non-myogenic stem cells in mouse Sk-MSCs [34]. However, the results clearly indicated that synergistic effects and/or specific adverse effects were not observed in the mixed group, which showed comparable results to those of the Sk-34 group in all experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This mixture was actually the same as for mouse Sk-MSCs [8], because it is difficult to divide myogenic and non-myogenic stem cells in mouse Sk-MSCs [34]. However, the results clearly indicated that synergistic effects and/or specific adverse effects were not observed in the mixed group, which showed comparable results to those of the Sk-34 group in all experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Factors and their primer sets are summarized in Table 1. Detailed methods for RT-PCR were as described previously [1,21]. Briefly, sheet-pellets were lyzed and total RNA was purified using a QIAGEN RNeasy micro kit (Hilden, Germany).…”
Section: Characterization Of Stem Cell Sheet-pellets Using Rt-pcrmentioning
confidence: 99%
“…At that time, CD45 + cells were blood stream derived hematopoietic cells, thus, they were discarded. Recently, we found that most of the colony-forming unit of Sk-DN cells showed positive for CD29 (also known as β1-integrin), thus, their positive selection as CD34 -/CD45 -/CD29 + (Sk-DN/29 + ) is a much more practical way 21) . The current sorting pattern is shown in Fig.…”
Section: The Role Of Muscle Fiber Blmentioning
confidence: 99%
“…1H). It is important to note that cells and/or myotubes in Sk-DN and Sk-34 cell cultures typically show active and spontaneous contraction supplemental movies in 10, 21,52) . More importantly, this clonal culture suggests that the formation of numerous multinucleated myotubes can be derived from single Sk-DN and Sk-34 cells (clones).…”
Section: The Role Of Muscle Fiber Blmentioning
confidence: 99%
See 1 more Smart Citation